Health Management of Humpback Grouper Larvae (Cromileptes altivelis) in BBRBLPP Gondol - Muh Sulaiman Dadiono; Indra Suryawinata (Journal of Aquaculture Development and Environment, 2022)
Larvae health management is a key factor in the hatchery of humpback grouper (Cromileptes altivelis) to prevent mass larval deaths and cause financial losses. Management of humpback grouper larvae health includes larval rearing, larval feed management and larval disease control. The primary data collection method was carried out in 3 ways, namely observation, active participation and interviews. Secondary data retrieval by studying literature from various related sources. The humpback grouper larvae were reared in the hatchery to control the temperature and condition of the larvae. Larval ponds are sterilized with 3-5 ppm chlorine in the morning and rinsed thoroughly so that no chlorine remains. Larvae were reared from the age of 1 day to 45 days. Feeding the larvae was started when the larvae were 2 days old with Nannochloropsis occulata. Rotifers were given when the larvae were 2-3 days old with a density of 5 individuals/ml. Artemia was given when the larvae were 20 days old until the age of 40 days. Pellets are given when the larvae are 8-10 days old with a pellet size of level 1. The pellet size continues to increase according to the larva's mouth opening. The disease that often attacks larvae is Viral Nervous Necrosis (VNN). The characteristics of larvae infected with VNN are reduced appetite, weak movement, larvae float on the surface and lie on the bottom of the pond. VNN attacks can only be overcome by prevention. The bacteria that often attack the larvae are Vibrio alginolyticus. Vibrio alginolyticus can be treated with antibiotics or non-antibiotics. The use of antibiotics is not recommended because they have negative side effects, so you can use other alternative medicines derived from herbal plants (phytopharmaceuticals).